International Jurisdiction under the EU Property Regimes Regulations – Bringing Coherence into Cross-Border Couples’ Property Disputes (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
The paper thoroughly examines the rules on jurisdiction of the Property Regimes Regulations, analysing both the expected benefits as well as the existing and potential problems in the application of the new rules. The main accomplishment of the Property Regimes Regulations in the field of jurisdiction is that they established more coherence in the cross-border family law adjudication. Namely, they align the international jurisdiction regarding the couple’s property to that of the situation at the origin of the need to adjudicate on such property, i.e. separation of the couple or else the death of one of the spouses or partners. Such joinder of proceedings is the general rule in the Property Regimes Regulations and even mandatory when succession proceedings are pending.Questions concerning property relations between spouses or registered partners must, however, sometimes be resolved without an underlying separation or succession proceedings and Property Regime Regulations also provide for the international jurisdiction of courts in such “independent” cases. The main connecting factor is then the common habitual residence of the spouses or registered partners, in line with the general tendency in EU Private International Law of enhancing the importance of the habitual residence, rather than of the nationality.